Correlation between Magnetic Resonance Imaging Characteristics, Operative Findings, and Histopathology of Intracranial Meningioma - Giri, Niraj; Jha, Rajiv; Shrestha, Rajendra; Rajbhandari, Binod; Aryal, Sameer; Bhattarai, Sushil Mohan; Khadka, Namrata; Karki, Anjan Singh; Adhikari, Prakash Chandra; Rajbhandari, Sulabh; Chaurasia, Pooja; Bimali, Aayush; et al. (Journal of Multidisciplinary Research Advancements, 2026)
Meningiomas are the most common primary intracranial tumors, with surgical resection as the mainstay of treatment. Preoperative prediction of tumor consistency remains a challenge in neurosurgical planning. This study evaluated the correlations among MRI characteristics, intraoperative consistency, and histopathology in intracranial meningiomas. An analytical study was conducted in ninety patients undergoing resection at the National Neurosurgical Referral Centre, NAMS, Bir Hospital, using a convenience sampling method. Preoperative MRI (T1, T2, FLAIR sequences, contrast patterns), intraoperative consistency, and histopathology were recorded. Statistical analysis included chi-square tests and logistic regression (SPSS v26). T2 hypointensity strongly predicted hard tumors (OR=8.9, p<0.001), while T2 hyperintensity correlated with soft tumors (71%). FLAIR hypointensity provided additional predictive value (OR=3.2, p=0.02). Rim enhancement was highly specific for anaplastic meningiomas. Soft tumors achieved higher Simpson I/II resections (93.8%) compared to hard tumors (58.8%). WHO Grade I tumors had significantly better resection outcomes than Grade III (p<0.001). Preoperative MRI, particularly T2-weighted imaging, reliably predicts meningioma consistency and correlates with surgical outcomes, aiding operative planning and patient counselling.